Furnishing Nature: Textile Materiality and the Victorian Home in Alfred Hayes’s The Vale of Arden and Other Poems (1895) - Stefanie John (Cahiers Victoriens et Edouardiens)
This article examines the conjunction of environmental aesthetics, textile materiality, and notions of the home in the work of the British poet and translator Alfred Hayes (1857–1936). Hayes, who authored six collections of poems, has been largely neglected in studies of Victorian poetry, yet his pastoral and religious verse was popular among Victorian and Edwardian readers. Hayes was also closely affiliated with the fin-de-siècle literary scene. He contributed to The Yellow Book, collaborated with Richard Le Gallienne and Norman Gale, and was reviewed by Oscar Wilde. The essay investigates the forms and functions of Hayes’s textile references and allusions to Victorian interiors in the collection The Vale of Arden and Other Poems, which was first published by John Lane at The Bodley Head in 1895. Its lyrics weave together depictions of rural England as a home with imagery inspired by the textures of luxurious fabrics and furnishing objects, thus testing the boundaries of exteriority and interiority. The article first surveys the contents, potential influences, and material design of Hayes’s little-researched book. It links Hayes’s use of poetic form and imagery to late Victorian understandings of organicism in Arts and Crafts design and home decoration. At the centre of the article will be a close reading of Hayes’s poem ‘My Study’. The poem portrays an idyllic landscape as the speaker’s study. It alludes to conceptions of the ‘house beautiful’ and the ‘book beautiful’ as it combines ecopoetic and religious notions of nature as a domestic space and as a site of learning. The article argues that textile ecologies are central to Hayes’s negotiation of relationships between nature and artifice, enabling a distinctive fusion of traditional English pastoral and fin-de-siècle aestheticism. The eco-aesthetic meditations of Hayes’s poetry highlight conceptual links between nature and notions of the dwelling space (‘oikos’), and, at the same time, suggest that material culture, specifically the fin-de-siècle craze for beautiful objects and textures, furnished Victorian nature poetry.